Pengaruh Transfer Pricing terhadap Penghindaran Pajak Perusahaan Sektor Industri di Indonesia - Dini Purnamasari; Novia Hindayani (Jurnal Ilmiah Raflesia Akuntansi, 2026)
Abstrak— This study aims to analyze the effect of transfer pricing on tax avoidance in industrial sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Transfer pricing is often perceived as a mechanism used by multinational companies to shift profits to low-tax jurisdictions, thereby potentially reducing their tax burden. The research employs a quantitative method using a simple linear regression approach. Secondary data were obtained from the companies’ annual financial reports. The results show that transfer pricing has no significant effect on tax avoidance. This finding indicates that transfer pricing practices among industrial sector companies in Indonesia have not been aggressively used as a means of tax avoidance. This study implies that the government should continue strengthening transfer pricing documentation policies, while companies are encouraged to maintain tax compliance as part of sound corporate governance practices.